Tradisi Kematian Wong Islam Jawa - Suwito Suwito; Agus Sriyanto; Arif Hidayat (IAIN Purwokerto, 2014)
Abstract: This study was aimed at revealing how Javanese Moslem’s traditionsof mortality is understood by the performers, both of great and little tradition, andwhat their meanings are. These two points evolve from time to time. Some variationsfound in the tradition of Javanese Moslem’s mortality are caused by the distance ofthe performers from the center of governance and the different time of performance.In regards to these variations, there are some interesting views. First, in understandingtheir belief and performing their tradition of mortality, Javanese Moslems has aprinciple that the tradition is an expression of honor to human being and it has asymbolic meaning. Second, Javanese Moslem mean mortality as a return way toGod that requires sincerity and a belirf that God is the only to worship. JavaneseMoslems perceive that God is forgiveful that human beings should pray and apologizefor their mistakes.Key words: tradition, Javanese Islam, variation, God, and Faith. Abstrak: Tulisan ini berusaha untuk mengungkap tentang tradisi kematian WongIslam Jawa dipahami oleh pelakunya dalam framework great and little tradition, danmakna di dalam tradisi kematian Wong Islam Jawa. Dua hal tersebut, bila diungkap dandipahami dalam tataran praktik, adakalanya memiliki pergeseran. Variasi yang munculdalam tradisi kematian Wong Islam Jawa karena jarak yang jauh dari pusat, juga karenaperubahan dari waktu ke waktu (evolusi). Dalam hal ini, ada beberapa pandangan menarik:Pertama, Wong Islam Jawa dalam memahami keyakinan dan menjalankan praktiktradisi kematian memiliki dasar yang leluhur sebagai tata cara penghormatan kepadamanusia yang hidup, serta memiliki dimensi simbolik dengan alam lain. Kedua, WongIslam Jawa dalam memaknai kematian sebagai jalan kembali kepada Tuhan sehinggaharus dalam keadaan suci dan tetap memiliki keyakinan bahwa Allah SWT adalah satusatunyayang pantas disembah. Pandangannya berdasar pada Tuhan YangMahapengampun sehingga manusia hendaknya senantiasa berdoa untuk minta maafatas kesalahan yang pernah diperbuat.Kata Kunci: tradisi, Wong Islam Jawa, variasi, Tuhan, dan keyakinan.